Skip to content

Commit

Permalink
doc(pm): working document on math for modal model
Browse files Browse the repository at this point in the history
  • Loading branch information
mchitre committed Jan 11, 2025
1 parent cfdfeb7 commit 55137fa
Showing 1 changed file with 113 additions and 0 deletions.
113 changes: 113 additions & 0 deletions docs/misc/modes.md
Original file line number Diff line number Diff line change
@@ -0,0 +1,113 @@
# Mode propagation in a Pekeris waveguide

This math is largely based on `kraken.pdf` by Michael B. Porter.

## Basic theory

The acoustic wave equation is:
$$
\nabla^2p = \frac{1}{c^2}\frac{\partial^2p}{\partial t^2}.
$$
In a Pekeris waveguide with a pressure-release surface and a pressure-release bottom (good approximation for a long range propagation problem, as it turns out), the boundary conditions in cylindrical coordinates are:
$$
\begin{align*}
p(r,0) &= 0 \quad \forall \; r, \\
p(r,-D) &= 0.
\end{align*}
$$
For a monochromatic source of frequency $f$ Hz located at $(0,-z_s)$ boundary condition is:
$$
p(0,-z_s) = -A\exp(-i\omega t),
$$
where $A$ is the source amplitude, and $\omega = 2\pi f$. Due to symmetry of the Pekeris waveguide, we have dropped the azimuthal coordinate.

The wave equation with these boundary conditions admits an approximate modal solution of the form:
$$
p(r,z,t) = \frac{i}{4}\sum_m\psi_m(z_s)\psi_m(z)H_0^{(1)}(k_mr)\exp(-i\omega t),
$$
where $\psi_m(z)$ is the mode of order $m$ and $H_0^{(1)}$ is the Hankel function of the first kind and order 0, $k_m$ is the horizontal wavenumber associated with mode. The mode $\psi_m$ is given by:
$$
\psi_m(z) = \sqrt{\frac{2}{D}}\sin(\gamma_m z),
$$
where $\gamma_m$ is the vertical wavenumber associated with mode $m$:
$$
\gamma_m = \sqrt{k_0^2 - k_m^2},
$$
for wavenumber $k_0 = \omega/c$.

$\gamma_m$ is chosen to ensure boundary conditions are satisfied:
$$
\psi_m(0) = \psi_m(D) = 0,
$$
i.e.,
$$
\gamma_m = m\frac{\pi}{D}.
$$
If the bottom boundary condition is chosen for a rigid bottom:
$$
\begin{align*}
& \left.\frac{d}{dz}\psi_m(z)\right|_{z=D} = 0, \\
& \therefore \; \gamma_m = \left(m-\frac{1}{2}\right)\frac{\pi}{D}.
\end{align*}
$$

Substituting $\psi_m$ back, we have:
$$
p(r,z,t) = \frac{i}{2D}\sum_m\sin(\gamma_m z_s)\sin(\gamma_m z)H_0^{(1)}(k_mr)\exp(-i\omega t),
$$
The transmission loss is then given by:
$$
\text{TL}(r,z) = -20\log\left| \frac{p(r,z)}{p^0_{r=1}} \right|,
$$
where $p^0_{r=1}$ is the pressure due to the source at 1 m from the acoustic center of the source:
$$
p^0_{r=1} = \frac{\exp(ik_0r)}{4\pi r} = \frac{\exp(ik_0)}{4\pi}.
$$

## Acousto-elastic boundary condition

If we use an acousto-elastic boundary condition for the seabed with sound speed $c_b$ and density $\rho_b$, we have a boundary condition:
$$
\left.\rho_b\frac{d\psi_m}{dz}\right|_{z=D} = -\rho\sqrt{k_m^2 - k_b^2} \; \psi_m(r,D).
$$
for $k_b = \omega/c_b$. Substituting $\psi_m(r,z)$:
$$
\rho_b\gamma_m\cos(\gamma_m D) + \rho\sqrt{k_m^2 - k_b^2} \; \sin(\gamma_m D) = 0.
$$

## Group velocity

The group velocity of mode $m$ is $d\omega/dk_m$. Given:
$$
\begin{align*}
k_m^2 &= k_0^2 - \gamma_m^2 \\
\therefore \; 2k_m\frac{dk_m}{d\omega} &= \frac{2k_0}{c} - 2\gamma_m\frac{d\gamma_m}{d\omega} \\
\therefore \; \frac{dk_m}{d\omega} &= \frac{k_0}{c k_m} - \frac{\gamma_m}{k_m}\frac{d\gamma_m}{d\omega}
\end{align*}
$$
Also:
$$
\begin{align*}
&\rho_b\gamma_m\cos(\gamma_m D) + \rho\sqrt{k_m^2 - k_b^2} \; \sin(\gamma_m D) = 0 \\
\therefore \quad &\rho_b\gamma_m\cos(\gamma_m D) + \rho\sqrt{k_0^2 - \gamma_m^2 - k_b^2} \; \sin(\gamma_m D) = 0 \\
\therefore \quad &\rho_b\frac{d\gamma_m}{d\omega}\cos(\gamma_m D) - \rho_b\gamma_m\sin(\gamma_m D)D\frac{d\gamma_m}{d\omega} + \rho\zeta\cos(\gamma_m D)D\frac{d\gamma_m}{d\omega} \\
&- \frac{\rho}{2\zeta}\sin(\gamma_m D)\left(\frac{2k_0}{c} - 2\gamma_m\frac{d\gamma_m}{d\omega} - \frac{2k_b}{c}\right) = 0 \\
\therefore \quad &\left[\rho_b\cos(\gamma_m D) - \rho_bD\gamma_m\sin(\gamma_m D) + \rho D\zeta\cos(\gamma_m D) - \frac{\rho\gamma_m}{\zeta}\sin(\gamma_m D)\right]\frac{d\gamma_m}{d\omega} \\
&= -\frac{\rho k_0}{c\zeta}\sin(\gamma_m D) - \frac{\rho k_b}{c\zeta} \; \sin(\gamma_m D) \\
\therefore \quad &\frac{d\gamma_m}{d\omega} = -\frac{\rho\sin(\gamma_m D)(k_0 + k_b)}{c\zeta[\rho_b\cos(\gamma_m D) - \rho_bD\gamma_m\sin(\gamma_m D) + \rho D\zeta\cos(\gamma_m D) - \frac{\rho\gamma_m}{\zeta}\sin(\gamma_m D)]} \\
&= -\frac{\rho\sin (\gamma_m D)\omega\left(c^2-c_b^2\right)}{c^2 c_b^2 \gamma_m \sin (\gamma_m D) \left(D\text{$\rho $b} \zeta+\rho \right)+\cos(\gamma_m D) \left(c^2 \left(D\rho\omega ^2-c_b^2 \text{$\rho $b} \zeta\right)-c_b^2 D\rho\omega^2\right)+c^2 c_b^2 D\rho\gamma_m^2\cos(\gamma_m D)}.
\end{align*}
$$
where $\zeta = \sqrt{k_0^2 - \gamma_m^2 - k_b^2}$.


Mathematica code to do the simplification:
```
Derivative[1][\[Gamma]][\[Omega]] /.
Solve[Collect[
D[\[Rho]b \[Gamma][\[Omega]] Cos[\[Gamma][\[Omega]] h] + \[Rho] \
Sqrt[(\[Omega]/c)^2 - \[Gamma][\[Omega]]^2 - (\[Omega]/
cb)^2] Sin[\[Gamma][\[Omega]] h], \[Omega]],
Derivative[1][\[Gamma]][\[Omega]]] == 0,
Derivative[1][\[Gamma]][\[Omega]]][[1]] // Simplify
```

0 comments on commit 55137fa

Please sign in to comment.